Tantangan dan Kontroversi terhadap Dampak Serta Implikasi dalam Implementasi PP No. 35 Tahun 2023 - Ayaturrohmah Fijihadi; Nynda Fatmawati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
On 16 Juni 2023, the new government amended the previous law on Taxation and Redistributing Districts (BPHTB) to include all rights of land and property (exchange, grant, inheritance, land income into the company, etc.). The aim is to optimize the distribution of land through BPHTB. The critical passage in the PP is Pasal 18 ayat 2, which defines the conditions for BPHTB, including the creation of a legal authority, the right to be a wari, the right to be a judge, the right to be a judge, the right to be a judge, the right to be a judge, the right to be a judge, the right to be a judge, and the right to be a judge. The study uses normative research to analyze the PPAT's role in determining the status of BPHTB and its impact on the law. The study also examines the legal resertact process, which involves examining the law's consistency with the law and the legal norms.